In vitro Activity of Ceftaroline Against Pathogens Collected Globally from the AWARE Surveillance Program, 2016. (4th October 2017) - Hackel, Meredith; Iaconis, Joseph; Sahm, Dan
Abstract: Background: Ceftaroline, the active metabolite of ceftaroline fosamil, is a cephalosporin developed for treating infections caused by Staphylococcus aureus, including methicillin-resistant S. aureus (MRSA), Streptococcus pneumoniae, β-hemolytic streptococci, and some Gram-negative pathogens. This study reports the in vitro activity of ceftaroline against clinically relevant isolates collected in 2016 from the AWARE Surveillance Program. Methods: 22, 752 non-duplicate methicillin-sensitive S. aureus (MSSA), MRSA, S. pneumoniae, β-hemolytic streptococci ( S. pyogenes, S. agalactiae, S. dysgalactiae ) Haemophilus influenzae, and extended spectrum β-lactamase (ESBL)-negative Enterobacteriaceae were collected from (n/%) Asia/South Pacific (4, 215/18.5%), Europe (12, 962/57.0%), Latin America (3, 384/14.9%), and Middle East/Africa (2, 191/9.6%) during 2016. Isolates were from (n/%) complicated intraabdominal (2, 149/9.5%), complicated urinary tract (3, 029/13.3%), complicated skin and skin structure (8, 271/36.4%), blood stream (2, 422/10.6%) and lower respiratory tract infections (6, 881/30.2%). MIC values were determined by broth microdilution and interpreted using CLSI breakpoints. Results: Ceftaroline activity, based on % susceptibility (%S) and MIC90, is shown in the table. Ceftaroline was active in vitro against both Gram-positive (100% of MSSA, 93.6% of MRSA and 99.7% of S. pneumoniae ) and Gram-negative (99.7% of H. influenzae and 91.7% of ESBL-negative Enterobacteriaceae ) isolates. Conclusion: Based on these data generated with isolates collected in 2016, ceftaroline exhibited potent in vitro activity against clinically relevant isolates, with >91% of all isolates susceptible at their CLSI breakpoints. Funding: This study was sponsored by AstraZeneca. The AstraZeneca product ceftaroline fosamil was acquired by Pfizer in December 2016. Disclosures: J. Iaconis, AstraZeneca: Employee and Shareholder, Salary and Shareholder in AstraZeneca